Euroization in Central, Eastern and Southeastern Europe – New Evidence On Its Extent and Some Evidence On Its Causes - Thomas Scheiber; Helmut Stix (Oesterreichische Nationalbank (OeNB), 2009)
We present new evidence on de facto euroization in eleven Central, Eastern and Southeastern European countries. Estimates of the extent of foreign currency cash holdings are derived from survey data. Furthermore, we define overall euroization indices, relating both assets and cash holdings. Results confirm that some countries are heavily euroized and that euro cash holdings constitute a sizeable share of local currency in circulation. Euroization levels in other –mainly Central European– countries are low and economically insignificant. Evidently, high euroization bears various significant consequences for economic policies. Therefore, we inquire on the determinants of euroization. We find that euroization is highly correlated with the quality of past economic governance, reflecting past periods of instabilities. In contrast, the more recent –pre-financial crisis– course of economic history had only limited impact. Thus, our results are in line with the view that policy makers in highly euroized countries are severely constrained by past events and that euroization levels might be difficult to revert through stable macroeconomic policies.
Keywords: E41; E50; D14; 330; Dollarization; Euroization; Currency Substitution; Survey Data; Central; Eastern; Southeastern; Europe; CEE; SEE